13th Pacific Rim International Symposium on Dependable Computing (PRDC 2007) 2007
DOI: 10.1109/prdc.2007.34
|View full text |Cite
|
Sign up to set email alerts
|

Soft Error Rate Estimation in Deep Sub-micron CMOS

Abstract: Soft errors resulting from the impact of charged particles are emerging as a major issue in the design of reliable circuits at deep sub-micron dimensions. In this paper, we model the sensitivity of individual circuit classes to Single Event Upsets using predictive technology models over a range of CMOS device sizes from 90nm down to 32nm. Modeling the relative position of particle strikes as injected current pulses of varying amplitude and fall time, we find that the critical charge for each technology is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…By decreasing the semiconductor size, the collected charge required to upset the logic also decreases and becomes susceptible to soft errors. Similarly, critical charge has been confirmed to decrease under lower operating voltages and smaller feature sizes [11]. Reference [12] confirmed that the SER is altered depending on several factors, including the critical charge.…”
Section: Critical Chargementioning
confidence: 83%
“…By decreasing the semiconductor size, the collected charge required to upset the logic also decreases and becomes susceptible to soft errors. Similarly, critical charge has been confirmed to decrease under lower operating voltages and smaller feature sizes [11]. Reference [12] confirmed that the SER is altered depending on several factors, including the critical charge.…”
Section: Critical Chargementioning
confidence: 83%
“…An increase in the pMOS width from its minimum value (0.12 μm) up to 0.22 μm provides a critical charge increase of almost 40% (38.35%). (To get a relative perspective, data reported in [18] show that the Q crit degradation with technology scaling from 90-nm technology down to the 32-nm node ranges between 39% and 44% per technology jump.) If the Vt configuration is kept unchanged (i.e., PS-NS), the write stability degradation is as large as 20%, while read stability improves by 7%.…”
Section: Discussionmentioning
confidence: 99%
“…εξαρτάται από την τοποθεσία της πρόσκρουσης. Δηλαδή μια πρόσκρουση κοντά στον κόμβο υποδοχής παράγει έναν παλμό μικρής διάρκειας και υψηλής αιχμής, ενώ μια πρόσκρουση μακριά από αυτόν παράγει έναν παλμό μεγάλης διάρκειας και χαμηλής αιχμής [25]. Συνήθως ο χρόνος ανόδου είναι μικρός (μεταξύ 0.1ps και 10ps) και ο χρόνος καθόδου μεγαλύτερος (μεταξύ 10ps και 200ps).…”
Section: μοντελοποίηση διαταραχής λόγω ακτινοβολίαςunclassified